Biomass Assessment of Peach Trees in the Ecuadorian Andes - Velázquez-Martí, Borja; Vega Chariguaman, Jorge Efraín; Gutiérrez Albán, Alberto Cristobal; Cazco-Logroño, Carlos; Chandi Mora , Henry Rolando (ACI Avances en Ciencias e Ingenierías, 2022)
This work focused on the evaluation of four essential aspects of biomass based on peach trees grown in the Andean region of Ecuador. In one case, mathematical models have been developed allowing the amount of lignocellulosic material to be quantified from easily measurable parameters such as crown diameter, stem diameter and plant height. Performing quick surveys, these equations led to obtain the amount of biomass contained in a plot. In a second case, elemental analysis of biomass was performed in order to determine the amount of CO2 captured from the atmosphere through photosynthesis during its growth, and thus to assess the contribution of these plots in mitigating climate change. Afterwards, residual biomass from pruning was quantified and a proximal analysis was carried out. This allowed us to assess the suitability of these materials as solid biofuels. The models obtained to determine the volume of the branches gave determination coefficients of 0.98. Models to quantify the biomass of the whole plant had r2 of 70%. The density of the dried material was 0.92 g/cm3, obtaining an average dry wood weight of 44.8 kg per plant. This represents a content of 1682 moles of captured CO2 of a developed plant crop (3 years). The average ash on dry wood was 3%, fixed carbon content on dry wood was 7%, and volatile content dry wood was 78%. The moisture content of waste materials after pruning was 45.96%. The drying time in store for humidity below 10%, suitable for burning boiler, was 15 days. The higher heating value of peach wood was 18.92MJ/kg.